2008
DOI: 10.1002/jcb.21762
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and nuclear localization of thioredoxin‐1 in sparse cell cultures

Abstract: Reactive oxygen species (ROS) were once viewed only as mediators of toxicity, but it is now recognized that they also contribute to redox signaling through oxidation of specific cysteine thiols on regulatory proteins. Cells in sparse cultures have increased ROS relative to confluent cultures, but it is not known whether protein redox states are affected under these conditions. The purpose of the present study was to determine whether culture conditions affect the redox state of thioredoxin-1 (Trx1), the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status. In any case, we observed that PMA induced an increase in TRX-1 non-fully oxidized forms, which was prevented by apocynin.…”
Section: Discussioncontrasting
confidence: 62%
“…In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status. In any case, we observed that PMA induced an increase in TRX-1 non-fully oxidized forms, which was prevented by apocynin.…”
Section: Discussioncontrasting
confidence: 62%
“…Another example is the support of peroxiredoxin activity and other antioxidant functions that counteract the triggering of apoptosis through oxidative stress. It is interesting to note that the levels of Trx1 are higher in confluent cultures than in sparse cultures of HeLa cells (38). Other stress response proteins have been shown to increase as cells reach confluence including MnSOD (39) and NADH cytochrome b 5 reductase (40), but the increase of Trx1 seems particularly relevant to the decrease of reactive oxygen species that is also observed in confluent cells (38,40).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the levels of Trx1 are higher in confluent cultures than in sparse cultures of HeLa cells (38). Other stress response proteins have been shown to increase as cells reach confluence including MnSOD (39) and NADH cytochrome b 5 reductase (40), but the increase of Trx1 seems particularly relevant to the decrease of reactive oxygen species that is also observed in confluent cells (38,40). These previous data could give a supportive explanation for our observation that decreased Trx activity in confluent cultures of SlrP expressing cells is correlated with increased cell death (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Trx1 is functionally autonomous from cytoplasmic Trx1. A distinct nuclear existence of Trx1 has been demonstrated by immunohistochemical studies, suggesting that Trx1 is imported into the nucleus during oxidative stress (69,169,177,197). Spielberger et al (177) found that cells in sparse culture have increased ROS level, and oxidation of both Trx1 and GSH redox states.…”
Section: Nuclear Thioredoxin Systemmentioning
confidence: 99%
“…A distinct nuclear existence of Trx1 has been demonstrated by immunohistochemical studies, suggesting that Trx1 is imported into the nucleus during oxidative stress (69,169,177,197). Spielberger et al (177) found that cells in sparse culture have increased ROS level, and oxidation of both Trx1 and GSH redox states. In sparse cultures, nuclear localization of Trx1 was high relative to high-density cultures, indicating that the redox environments of the cytoplasm and the nucleus are distinct and that Trx1 has an important role of nuclear redox state in cell growth.…”
Section: Nuclear Thioredoxin Systemmentioning
confidence: 99%